Service Quality of Child Identity Card Issuance via Plavon Dukcapil: Kualitas Layanan Penerbitan Kartu Identitas Anak melalui Plavon Dukcapil - Mochamad Khoirudin Afid; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Population growth in Indonesia increases demand for accessible and efficient public services, particularly in population administration and civil registration. Specific Background: The Population and Civil Registration Office of Sidoarjo Regency implemented the web-based Plavon Dukcapil system to facilitate administrative services, including Child Identity Card issuance as an essential legal identity document for children. Knowledge Gap: Although digital services have been introduced, concerns remain regarding service infrastructure, procedural delays, and limited public awareness of administrative service procedures. Aims: This study aims to describe the quality of population administration services through Plavon Dukcapil, focusing on Child Identity Card services using the service quality dimensions of Zeithaml, Parasuraman, and Berry. Results: Using a descriptive qualitative approach, the study shows that tangible aspects indicate professional staff performance and adequate supporting facilities, although waiting seating remains limited. Reliability reflects clear service procedures but delays in document publication due to incomplete submissions and system disruptions. Responsiveness demonstrates fast complaint handling through hotlines and social media, despite limited direct public socialization. Assurance confirms cost-free services and secure management of population data, strengthening public trust. Empathy reveals friendly and non-discriminatory staff providing clear guidance to service users. Novelty: This study provides an integrated evaluation of digital population administration services through Plavon Dukcapil by applying a multidimensional service quality framework to Child Identity Card services. Implications: The findings emphasize the importance of improving service facilities, system stability, and public socialization to support sustainable digital public service delivery. Highlights: Professional staff conduct and adequate infrastructure support administrative processing, yet seating capacity remains insufficient during peak visits. Clear operational procedures exist, but document verification and system disruptions contribute to processing delays. Cost-free processing and protected demographic records strengthen public trust and user satisfaction. Keywords: Service Quality, Child Identity Card, Plavon Dukcapil, Population Administration Services, Public Service Innovation